Evaluation of a Novel Point-of-Care Ultrasound Curriculum for First-Year Pediatric Residents. Issue 11 (17th November 2022) - Hulse, Whitley N.; Bell, Colin R.; Roosevelt, Genie E.; Sabbadini, Linda; Germano, Rocco; Hopkins, Emily; Kendall, John; Toney, Amanda G.
Abstract : Objective: The aim of the study is to evaluate a novel point-of-care ultrasound (POCUS) educational curriculum for pediatric residents. Methods: The cohort study in graduate medical education was completed from January 2017 to March 2019. Postgraduate year 1 (PGY1) pediatric residents attended the educational curriculum that consisted of 3 half-day sessions over a 3-month period. Each session consisted of a lecture (introduction, extended focused assessment with sonography for trauma, soft tissue/musculoskeletal, cardiac, and resuscitative applications) followed by supervised hands-on scanning sessions. Group ratio was 3 learners to 1 machine/expert instructor. Main outcome measures included pre– and post–written test scores, as well as objective structured clinical examination (OSCE) scores. Results: Forty-nine PGY1 residents (78% women) completed the curriculum. The mean (SD) pretest score was 68% (8.5), and the mean posttest score was 83% (8.3) with a difference of 15 (95% confidence interval, 12.5–17.6; P < 0.001). Mean (SD) focused assessment with sonography for trauma OSCE score after the curriculum was 88.7% (11.9). The number of PGY1 pediatric residents that were comfortable performing POCUS examinations increased from pretraining to posttraining for soft tissue/musculoskeletal (14%–61%, P < 0.001), extended focused assessment with sonography for trauma (24%–90%, P < 0.001), and cardiac (18%–86%, P < 0.001). All participants found the curriculum useful, and 42 of 49 (86%) stated the curriculum increased their ability to acquire and interpret images. Conclusions: Postgraduate year 1 pediatric residents learned the basics of POCUS through 3 brief educational sessions. The increase in posttest scores demonstrated improved POCUS knowledge, and the high OSCE score demonstrated their ability to acquire ultrasound images. Point-of-care ultrasound guidelines are needed for pediatric residency programs.